CEREBELLAR TDCS AND GAIT TRAINING IN CHILDREN WITH DOWN SYNDROME: A RANDOMIZED, DOUBLE-BLIND, PLACEBO-CONTROLLED CLINICAL TRIAL (CIPEEX, 2025)
Introduction: Down syndrome (DS) is associated with gait and balance impairments. Task-oriented rehabilitation strategies, such as treadmill training, have demonstrated benefits. Cerebellar transcranial direct current stimulation (tDCS) has emerged as a promising adjuvant to gait training, although it remains unexplored in DS. Objective: To evaluate the efficacy of anodal cerebellar tDCS combined with treadmill training on mobility, gait, and balance in children with DS. Methods: A randomized, double-blind, placebo-controlled clinical trial was conducted with 11 children with DS. Participants underwent 10 sessions of treadmill training combined with either active tDCS (1 mA, 20 min, anode over the cerebellum) or sham stimulation. Outcomes were assessed at three time points (baseline, post-intervention, and 4-week follow-up) and included functional mobility (Timed Up and Go – TUG), gait parameters (10-Meter Walk Test with inertial sensor), and functional balance (Pediatric Balance Scale – PBS). Results: All participants completed the protocol without relevant adverse events. In the TUG, a small effect size was observed post-intervention (d = 0.24) and a large effect size at follow-up (d = 1.80) favoring active tDCS. The experimental group showed increased gait velocity at follow-up (d = 1.3; p = 0.036) and improved balance performance, with a moderate effect post-intervention (d = 0.60) and at follow-up (d = 0.71; p = 0.008). Conclusion: Cerebellar tDCS combined with treadmill training was safe, feasible, and potentially effective in enhancing mobility and balance in children with DS, with preliminary evidence of short-term retention of gains.
Keywords: Down Syndrome; Child: Gait; Cerebellum; transcranial Direct Current Stimulation